DDX5 Silencing Suppresses the Migration of Basal cell Carcinoma Cells by Downregulating JAK2/STAT3 Pathway. (21st December 2019) - Quan, Zhe; Zhang, Bei-bei; Yin, Fang; Du, Jiru; Zhi, Yuan-ting; Xu, Jin; Song, Ningjing
Basal cell carcinoma is driven by the aberrant activation of hedgehog signaling. DEAD (Asp-Glu-Ala-Asp) box protein 5 is frequently overexpressed in human cancer cells and associated with the tumor growth and invasion. The purpose of this study was to investigate the role of DEAD (Asp-Glu-Ala-Asp) box protein 5 in the growth, migration, and invasion of basal cell carcinoma. The role of DEAD (Asp-Glu-Ala-Asp) box protein 5 was detected by quantitative real-time polymerase chain reaction, Western blot, and terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick-end labeling assay in basal cell carcinoma cells. The associations between JAK2/STAT3 pathway and DEAD (Asp-Glu-Ala-Asp) box protein 5 were analyzed in basal cell carcinoma cells. Results showed that DEAD (Asp-Glu-Ala-Asp) box protein 5 is overexpressed in basal cell carcinoma cells. DEAD (Asp-Glu-Ala-Asp) box protein 5 knockdown inhibited the migration and invasion of basal cell carcinoma cells. DEAD (Asp-Glu-Ala-Asp) box protein 5 knockdown increased the apoptosis of basal cell carcinoma cells induced by tunicamycin. Results found that DEAD (Asp-Glu-Ala-Asp) box protein 5 knockdown increased JAK2 and STAT3 expression in basal cell carcinoma cells. JAK2 inhibitor decreased STAT3 expression and abolished the inhibitory effects of DEAD (Asp-Glu-Ala-Asp) box protein 5 silencing on migration and invasion in basal cell carcinoma cells. In conclusion, these results indicate that DEAD (Asp-Glu-Ala-Asp) box protein 5 is a potential target for inhibiting basal cell carcinoma cells growth, migration, and invasion by downregulating JAK2/STAT3 pathway.